2021
DOI: 10.31234/osf.io/feuj9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parent–Child Conflict During Homeschooling in Times of the COVID-19 Pandemic: A key Role for Mothers’ Self-Efficacy in Teaching

Abstract: To contain the COVID-19 pandemic schools have been closed in many countries. Children stayed at home and were assisted by their parents with their schoolwork. Evidently, homeschooling puts extra demands on parents. We presumed that parents’ sense of self-efficacy in teaching would play a key role in how they cope with this extra task of homeschooling. In particular, we hypothesized that parental characteristics (social-economic status (SES) and Stress) and social-contextual factors (home chaos; school support)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Given the focus of the self-efficacy scale in the present study on parent support for the learning of their children, this finding is surprising. In fact, one study conducted with mothers of young children without disabilities during COVID-19 found a significant positive relationship between learning-related self-efficacy and perceived academic supports from school (de Jong et al, 2021). It may be that the social-emotional aspects that promote learning, such as motivation, interest, pro-social behaviours, and relationships, were more necessary or impactful for families during pandemic at-home learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the focus of the self-efficacy scale in the present study on parent support for the learning of their children, this finding is surprising. In fact, one study conducted with mothers of young children without disabilities during COVID-19 found a significant positive relationship between learning-related self-efficacy and perceived academic supports from school (de Jong et al, 2021). It may be that the social-emotional aspects that promote learning, such as motivation, interest, pro-social behaviours, and relationships, were more necessary or impactful for families during pandemic at-home learning.…”
Section: Discussionmentioning
confidence: 99%
“…They also hold and convey more positive beliefs about competency to their children, who in turn develop greater self-efficacy and ultimately experience better academic outcomes (e.g., Bandura et al, 1996;O'Sullivan et al, 2014;Tazouti & Jarlégan, 2019). Higher self-efficacy has also been found to be related to low parent-child conflict during school work (de Jong et al, 2021) and to be influenced by socio-economic and family-related variables. Some research has shown that parents of students with ADHD have lower self-efficacy for learning, (e.g., Ogg et al, 2020;Rogers et al, 2009); however, very little literature has explored the learning-related self-efficacy of parents of students with special education needs more broadly.…”
Section: Parent Self-efficacy For Supporting Learning During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, as teachers, mothers gained understanding and learned coping and benefiting skills for their dual function. In the context of the COVID 19 pandemic, de Jong et al (2021) noted that evidently the homeschooling of children had put extra demands on mothers who, according to Darmody et al (2020) and Moore et al (2020), assumed more responsibilities in the household. On the other hand, family stress involves stressors that affect the family such as physical and mental health concerns, economic, intensified child-parent relationships, and home schooling (Wu & Xu, 2020).…”
Section: Theoretical Lensmentioning
confidence: 99%
“…Disrupted family routines and increased parenting duties may lead parents to experience additional stress and face more daily parenting hassles. For example, evidence showed that both parents and children reported that irritation with family members as one of the most common daily difficulties during the COVID-19 pandemic ( Janssen et al, 2020 ); some studies also reported increased parent-children conflict due to lockdown orders ( de Jong et al, 2021 ; Grigoropoulos, 2021 ). Given that cumulative daily hassles were significant ( Crnic and Greeberg, 1990 ), the main aim of this study was to discover the daily parenting hassles with school closures and kindergarten shut downs during the COVID-19 pandemic lockdown and examine how these daily hassles contribute to parents' mental health.…”
Section: Introductionmentioning
confidence: 99%